Science Teaching: Scientific Literacy in a School Perspective - Dimenäs, Jörgen (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
The article highlights the professional teachers' understanding of what they see as the most important contents in science education. The aim of the study is based on conversations with professional teachers and how they understand what are the most central contents in science education. It is related to scientific language and importance for society. Their understandings are related to the importance of science in the society and to the language's importance to students' learning opportunities. The result of the study's interviews are analyzed on the basis of Basil Bernstein's concept of the horizontal and vertical discourse, which demonstrates the opportunities for pupils to approach a scientific content based on a contextual understanding. How science is taught is an important question in the aspect of students coming from different socioeconomic conditions and with different conceptions of the outside world and the science school discourse. In the present study the professional teachers' in particular stresses the importance of a holistic understanding of the content in science, the methodical aspects in science education and the consequences of science and technology development. To be science literate in a teaching context means that the students will get the capacity to use scientific knowledge, to identify questions and to draw evidence based conclusions in order to understand and help make decisions about the natural world and the changes made to it through human activity.